Technology of adaptive physical education for children aged 7-9 years with autism spectrum disorder - Tulegen Botagariyev; Svetlana Kubiyeva; Nurolla Mambetov; Alpysbay Aralbayev; Amangazy Syzdykov; Saniya Konisbayeva (International Journal of Evaluation and Research in Education (IJERE), 2025)
Analysis of the scientific and methodological literature indicates that the issue of scientific and methodological support for children with autism spectrum disorder (ASD) is insufficiently addressed, particularly for the age group of 7-9 years, which is the focus of this study. The aim of the research is to develop and empirically demonstrate a method for adaptive physical education for children with autism aged 7-9 years. The study involved 20 children attending a neurological rehabilitation center and a general education school. The methodology included the use of paired t-tests to compare indicators before and after the intervention. Key findings included significant improvements in physical indicators such as lung vital capacity (LVC), hand strength, and motor coordination. The practical significance of this research lies in the development of an effective adaptive physical education program that can be implemented in educational and rehabilitation institutions to support children with ASD. Future research prospects include increasing the sample size and conducting long-term observations to examine the sustainability of the obtained results.